If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6t + 4 = 34 Reorder the terms: 4 + -6t = 34 Solving 4 + -6t = 34 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -6t = 34 + -4 Combine like terms: 4 + -4 = 0 0 + -6t = 34 + -4 -6t = 34 + -4 Combine like terms: 34 + -4 = 30 -6t = 30 Divide each side by '-6'. t = -5 Simplifying t = -5
| -81bc+7bc= | | 16x-5=10x+19 | | 3x+12*3x-6=3 | | 3(x+4)3(x-2)=3 | | x^2+11x=28 | | 5[2x-7]=15x-10 | | c=ax+b | | 8xy-(x+2xy)+3x= | | 2(xy+2x)-3xy= | | 7x^4=21x^2 | | 8y-13x-8=4 | | -13xy+9y-9xy+18y= | | -xy+-9xy= | | 25ab-37ab= | | 3[x-2]=2x+6 | | 110-90= | | 50+60= | | 12a-14a=3 | | -4n-8/17=23 | | a+c/2x=b | | x^2+2x=37 | | 2[x+3]=x+10 | | 6(3.14)=3.14x | | 2x+6=x+10 | | 2/x=5/x-6 | | 211c=105 | | q+(-10)=2 | | (y/4)=-7 | | p-8/(1/2)=-3 | | 100g=20 | | 72n=9 | | (2x+3)+(-3x+1)= |